Post-eastern Mediterranean Transient Oxygen Decline in the Deep Waters of the Southeast Mediterranean Sea Supports Weakening of Ventilation Rates - Sisma-Ventura, Guy; Kress, Nurit; Silverman, Jacob; Gertner, Yaron; Ozer, Tal; Biton, Eli; Lazar, Ayah; Gertman, Isaac; Rahav, Eyal; Herut, Barak (Frontiers in Marine Science, 2021)
Long-term trends in oxygen, salinity and nutrients were followed in the Southeastern Mediterranean (SEMS) deep water masses from 2002-2020. Results show a net decrease in oxygen since 2008 of -0.5±0.1 μmol kg-1 yr-1 in the bathypelagic depths (1200 – 2000m). Multiannual variability in oxygen levels superimposed this trend, and is likely associated with variations in thermohaline fluxes. The 2020 mean oxygen concentration of 179.5±2.3 μmol kg-1 is comparable to the pre- Eastern Mediterranean Transient (EMT) mean value. The post-EMT signature is clearly demonstrated in both oxygen and salinity over the period of 2002-2013, but since 2014 it diminished, mainly due to mixing of the Aegean deep water mass with the overlying old Adriatic water mass. This trend reflects a switch back to the pre-EMT regime, characterized by a thermohaline homogeneity of the deep water column in the SEMS. The long-term decline of deep water oxygen levels is also accompanied by a corresponding increase in dissolved inorganic nutrients, supporting aging of the deep water masses. Our results suggest that ventilation of the SEMS deep water is currently occurring at a lower, pre-EMT rate, probably as a result of moderated deep water formation in recent time.